Simplify : 3"X"- 4"X"-overline(3"X"-5"Y")-3 {2"X"-(3"X"-overline(2"X"-3"Y"))} - Mathematics

Advertisements
Advertisements
Sum

Simplify : `3"x"-[4"x"-overline(3"x"-5"y")-3  {2"x"-(3"x"-overline(2"x"-3"y"))}]`

Advertisements

Solution

`3"x"-[4"x"-overline(3"x"-5"y")-3  {2"x"-(3"x"-overline(2"x"-3"y"))}]`

= 3x  − [4x − 3x + 5 − 3 {2x − (3x − 2x + 3y)}]

= 3x − [4x − 3x + 5y − 3 {2x − (x + 3y)}]

= 3x − [4x − 3x + 5y − 3 {2x − x − 3y}]

= 3x − [x + 5y − 6x + 3x + 9y]

= 3x − [−2x + 14y]

= 3x + 2x − 14y

= 5x − 14y

Concept: Simplification of Expressions
  Is there an error in this question or solution?
Chapter 11: Algebraic Expressions - Exercise 11 (E) [Page 147]

APPEARS IN

Selina Concise Mathematics Class 8 ICSE
Chapter 11 Algebraic Expressions
Exercise 11 (E) | Q 1.09 | Page 147
Share
Notifications



      Forgot password?
Use app×